Acid Attack: A Devastating Violence Against Women. Issue 2 (December 2020) - Ghosal, Banashree; Chattopadhyay, Chandrani
This article will explore the problem of acid attack as a gender-related crime. We analyse the socio-legal status of this crime as a form of violence in comparison of other forms of violence in the Indian context with the help of secondary data. The patriarchal notion of women is that the body is her only respect, and its violation is ultimate punishment. The number of acid attacks is increasing every passing year. The latest report of the National Crime Records Bureau (NCRB) 2016 recorded 283 incidents under the section of acid attack ('Living in the shadows'- A project for acid attack victims by Haryana State legal Services Authority). It revealed that the most of the reported acid attack cases are due to refusal of marriage or rejection of romance. We discuss the consequences of acid attack and the legal framework available to address this problem.